1991
DOI: 10.1111/j.1440-1819.1991.tb01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizures in the 4p‐ Syndrome: Report of Two Cases

Abstract: We report ictal phenomena in two patients with the 4p – syndrome captured on simultaneous video‐EEG monitor. One patient, diagnosed as having partial epilepsy, had complex partial seizures and hemiconvulsive status epilepticus. This was associated with more severe mental retardation. The second patient was diagnosed as having the West syndrome and exhibited tonic spasms with a cluster formation. We conclude that various types of epileptic seizures may occur in patients with the 4p ‐ syndrome, including grand m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Most cases have refractory epilepsy that begins at ages between 6 and 24 months (61-65). The seizure types include generalized tonic-clonic seizures (GTCSs) (63)(64)(65), tonic spasms (63), myoclonic seizures, atypical absences associated with eyelid myoclonia, eye deviation and mouth jerks, partial motor seizures (59), and complex partial seizures (63). The EEG was described in detail by Sgro et al (59), who found sequences of sharp-wave transients on a background of diffuse, high-voltage 3-to 4-Hz slow-wave discharges prominent over the biparietal and frontal regions and activated by eye closure.…”
Section: Deletion Of the Short Arm Of Chromosome 4 Del(4)(pter->p15andmentioning
confidence: 99%
“…Most cases have refractory epilepsy that begins at ages between 6 and 24 months (61-65). The seizure types include generalized tonic-clonic seizures (GTCSs) (63)(64)(65), tonic spasms (63), myoclonic seizures, atypical absences associated with eyelid myoclonia, eye deviation and mouth jerks, partial motor seizures (59), and complex partial seizures (63). The EEG was described in detail by Sgro et al (59), who found sequences of sharp-wave transients on a background of diffuse, high-voltage 3-to 4-Hz slow-wave discharges prominent over the biparietal and frontal regions and activated by eye closure.…”
Section: Deletion Of the Short Arm Of Chromosome 4 Del(4)(pter->p15andmentioning
confidence: 99%
“…In 1997, the critical region of WHS was defined as a 165‐kb locus in 4p16.3 (3). Those with WHS often have refractory seizures (4) and easily develop status epilepticus (SE) (5). In this study, we investigated seizure types, clinical courses, and reported effective treatments of epilepsy in WHS.…”
mentioning
confidence: 99%
“…In Table 1 author describes the EEG ®ndings in a slightly dierent manner, but there is obviously a common denominator. This becomes even more apparent when comparing published EEG tracings [8,17] directly. SgroÁ et al [17] were the ®rst to point out that these ®ndings seem to be characteristic for WHS.…”
Section: Discussionmentioning
confidence: 89%
“…In 1996, Clemens et al [5] discovered that PRDS is also caused by 4p deletions and it has been suggested since that WHS and PRDS are just dierent forms of expression of essentially the same syndrome [20], although this is not unequivocally accepted [14,15]. Seizures occur in 50%±100% of WHS [5,18,4] and 80% of PRDS [14] patients, but the electroclinical ®ndings have been reported in only a few cases [1,5,6,12,8,17]. In 1995, SgroÁ et al [17] described a stereotypic electroclinical pattern in four unrelated WHS patients that seemed to be characteristic for WHS.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation